A Sustainability Accounting Disclosure With Maqashid Sharia Perspective - Ulfi Kartika Oktaviana; Achmad Sani; Nanik Wahyuni (Cita konsultindo, 2024)
The goal of this study is to quantify the level of sustainability accounting disclosures from the standpoint of maqasid al-Shari'ah. In order to record Islamic banks' sustainability accounting performance, an index structure is created. This index evaluates the performance of Islamic banks by building on a number of earlier empirical investigations. Our examination of the sustainability accounting disclosures from a maqasid sharia perspective revealed that each bank in the sample disclosed how well it adheres to the fundamental principles and ideals of Islamic banking. The third consequence self is the one with the lowest number. The Islamic Bank Maldives has received the greatest ratings for the fourth, fifth, and sixth consequences; the overall top score goes to the second consequence, which is related to rights and stakeholders.